2020
DOI: 10.1094/phyto-08-18-0311-r
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling Is Suppressed inMagnaporthe oryzaeConidia byBacillus cereusHS24

Abstract: Rice yield is greatly reduced owing to rice blast, a polycyclic fungal disease caused by the ascomycete Magnaporthe oryzae. Previously, Bacillus cereus HS24, isolated from a rice farm, showed a strong antimicrobial effect toward M. oryzae. To better exploit it as a biocontrol agent, HS24 was studied for the mechanism that it uses to suppress rice blast. Conidium germination in M. oryzae was significantly inhibited by HS24, whereby inhibition reached 97.8% at the concentration of 107 CFU/ml. The transcription l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Bacillus species can indirectly inhibit phytopathogens through biocontrol strategies including the repossession of pathogenic iron by siderophores, the production of hydrolytic enzymes to degrade pathogenic cell walls, and the production of antibiotics to interfere with pathogenic respiration (Ahmad et al, 2017;Li et al, 2014;Li et al, 2017;Qi et al, 2017;Zhang and Sun, 2018). Huang et al (2020) isolated B. cereus HS24 from a rice farm; B. cereus HS24 could significantly reduce conidium germination by interfering with the M. oryzae Ca 2+ signaling pathway. SEM analysis revealed that B. amyloliquefaciens S170 and B. pumilus S9 degraded the hyphae and conidial cell walls of M. oryzae P131.…”
Section: Strainsmentioning
confidence: 99%
“…Bacillus species can indirectly inhibit phytopathogens through biocontrol strategies including the repossession of pathogenic iron by siderophores, the production of hydrolytic enzymes to degrade pathogenic cell walls, and the production of antibiotics to interfere with pathogenic respiration (Ahmad et al, 2017;Li et al, 2014;Li et al, 2017;Qi et al, 2017;Zhang and Sun, 2018). Huang et al (2020) isolated B. cereus HS24 from a rice farm; B. cereus HS24 could significantly reduce conidium germination by interfering with the M. oryzae Ca 2+ signaling pathway. SEM analysis revealed that B. amyloliquefaciens S170 and B. pumilus S9 degraded the hyphae and conidial cell walls of M. oryzae P131.…”
Section: Strainsmentioning
confidence: 99%
“…Microbial fungicides can not only reduce the occurrence of diseases, but also maintain the ecological equilibrium ( Zhou et al, 2019 ). Previous studies have reported that Bacillus cereus strains exhibited antifungal activity against M. oryzae in vitro or in vivo , which is expected to be developed as fungicides to control rice blast, such as the B. cereus HS24 ( Huang et al, 2020 ), B. cereus AR156 ( Jiang et al, 2020 ), and B. cereus KF822666 ( Hassan et al, 2019 ). These studies provided a background for the development of biocides.…”
Section: Introductionmentioning
confidence: 99%
“…The Bacisubin protein, produced by B. subtilis B-916 (Liu et al 2007) can cause the R. solani mycelia to enlarge and rupture, and the crude antifungal protein RY3 produced by B. amyloliquefacens RY3 can inhibit the germination of P. digitatum spores (Chen et al 2013). Finally, the protein produced by B. cereus HS24, can significantly inhibit conidium germination and mycelial growth in M. oryzae (Huang et al 2019).…”
Section: Discussionmentioning
confidence: 97%